Information Acquisition And Utilization As Determinants Of Organizational Effectiveness: A Study Of Managers In Large Scale Manufacturing Industries In Nigeria. - Popoola, S. O. (Archives of Business Research, 2018)
This study examined information acquisition and utilization as determinants of organizational effectiveness of managers in large-scale manufacturing companies specializing in industrial and domestic products in Nigeria. The questionnaire was used for data collection from the 360 sampled managers out of which 332 responded and the copies of their questionnaire were found valid for analysis. The study found that the studied companies had moderate organizational effectiveness. Information acquisition, information sources and services’ utilization had significant relationship with organizational effectiveness of the respondents. However, information acquisition, information sources and services’ utilization of the managers had significantly determined organizational effectiveness of the manufacturing companies specializing in industrial and domestic products in Nigeria. It was therefore recommended that the management and board of directors of the companies should encourage their managers to acquire relevant information and use it to improve their organizational effectiveness. In addition, corporate library staff should provide effective information services to the managers so as to improve organizational effectiveness of their companies.